1949
DOI: 10.2118/949127-g
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Capillary Character In Petroleum Reservoir Rock

Abstract: Improved apparatus, methods, and experimental techniques for dete,mining the capillary pressure-saturation relation are described in detaiL In this connection a new multi-core procedure has been developed which simplifies the experimental work in the study of relatively homogeneous reservoirs_ The basic theory concerning the Leverett capillary pressure function has been extended and has been given some practical application_ Some discussion is presented to indicate the relationship of relative permeability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

1969
1969
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 0 publications
1
51
0
2
Order By: Relevance
“…This fact was confirmed by Brown [4], and Rose and Bruce [5]. Guthrie and Greenberger [1] proposed a linear correlation of the water saturation with porosity and permeability at a constant value of capillary pressure.…”
Section: Introductionmentioning
confidence: 76%
“…This fact was confirmed by Brown [4], and Rose and Bruce [5]. Guthrie and Greenberger [1] proposed a linear correlation of the water saturation with porosity and permeability at a constant value of capillary pressure.…”
Section: Introductionmentioning
confidence: 76%
“…For ideal uniform and unconsolidated rocks, Leverett 1940 computed the value of this term to be about 5. However, Rose and Bruce 1949 showed that this term (F S τ 2 ) could vary from 5 to 100 in real reservoir rocks. Many investigators have attempted to calculate permeability from porosity by using Eq.…”
Section: Hydraulic Zonation Theorymentioning
confidence: 99%
“…According to Rose and Bruce (1949), the shape of the capillary pressure curves is the primary indication of pore geometry. High capillary pressure primarily shows the existence of small pores.…”
Section: Rock Typing From Pore Size Distributionmentioning
confidence: 99%